Hospital-acquired nephrotoxic exposures in the precipitation of acute kidney injury - A case series analysis and a call for more preventative nephrology practices - Macaulay Amechi Onuigbo; Eileen Samuel; Nneoma Agbasi (Society of Diabetic Nephropathy Prevention, 2017)
The frequency of hospital-acquired acute kidney injury has been increasing in recent years. It is associated with higher patient mortality, increased length of stay, increased cost of hospitalization and potentially is linked with an increased risk of developing chronic kidney disease and end-stage renal disease over time. Decreased renal perfusion, nephrotoxic medications, surgery, and radiographic contrast media remain the most common causes of hospital-acquired acute kidney injury. We present some recent cases of hospital-acquired acute kidney injury managed in the Renal Unit, Mayo Clinic Health System, Eau Claire, WI, USA and make a strong case for more preventative nephrology practices to mitigate, if not eliminate, the scourge of hospital-acquired acute kidney injury.